Optosensor based on multiwall carbon nanotubes and quantum dots incorporated into a molecularly imprinted polymer for ciprofloxacin detection - Naphat Yuphintharakun (Prince of Songkla University, 2019)
Thesis (M.Sc., Chemistry)--Prince of Songkla University, 2018